Penggabungan Dua ISP Guna Menstabilkan Koneksi Internet Dengan Metode Failover - Didik Kurniawan; Wisnu wardhana; Nikko Agustino Ito (Universitas Lampung, 2016)
This early (nowadays), Internet Service Provider has been growing rapidly. To choose Internet Service Provider is extremely difficult because every Internet Service Provider has its advantages and disadvantages as well. Some methods such as Failover, Per Connection Classifier, Round Robin, and several others are able to combine between an internet connection from several multiple Internet Service Provider. Failover method is being useful for separating between the Internet Service Provider that will be a priority connection and the backup connection. In this application two or more Internet Service Providers cooperate together to keep the Internet connection remain stable. By using the application, it is no longer difficult to handle the problem of bad Internet Service Provider.